Ionic liquid-mediated synthesis of metal nanostructures: Potential application in cancer diagnosis and therapy - Mahnaz Hassanpour; Mohammad Hassan Shahavi; Golnaz Heidari; Arun Kumar; Mehrab Nodehi; Farnaz Dabbagh Moghaddam; Mahsa Mohammadi; Nasser Nikfarjam; Esmaeel Sharifi; Pooyan Makvandi; Hasan Karimi Male; Ehsan Nazarzadeh Zare (Journal of Ionic Liquids, 2022)
Ionic liquids have developed as a new class of low-temperature molten salts which are formed of weakly corresponding cations and anions. Efforts to extend the ionic liquids applications across different research arenas have grown in recent years with growths in understanding and tailoring their physical, chemical, and biological properties. The use of ionic liquids as a source/media for the synthesis and stabilization of metal nanostructures has gained more popularity recently owing to their ability to be personalized in varying sizes, and morphologies. The metal nanostructures synthesized in the presence of ionic liquids are employed in cancer diagnosis and therapy. The current review describes the different ionic liquids and their role in the synthesis of metal nanostructures for cancer diagnosis and therapy. In the end, the perspective and new directions for developing ionic liquid-mediated synthesis of metal nanostructures for cancer diagnostic and therapy are highlighted.